2020
DOI: 10.3389/fphar.2020.532395
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Esophageal Cancer Stem-like Cells by SNX-2112 Is Enhanced by STAT3 Silencing

Abstract: Many studies have demonstrated that cancer stem cells (CSCs) or tumor-initiating cells (TICs) are responsible for tumor cell proliferation, chemotherapy resistance, metastasis, and relapse in various cancers. We, and others, have previously shown that the signal transducer and activator of transcription 3 (STAT3) signaling pathway is responsible for CSCs and TICs growth. Recent reports have indicated that the heat shock protein 90 (Hsp90) is also essential for the survival of CSCs and TICs. SNX-2112 is an Hsp9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Here the dual treatment strongly inhibits the proliferation of ECSLCs, induces G2/M phase arrest and apoptosis of ECSLCs, significantly decreases the colony formation ability and the colony size of ECSLCs compared with shSTAT3 and SNX-2112 alone ( 132 ). On a molecular point of view, the combined treatment reduces the levels of phosphorylation of Hsp90 client proteins involved in cell proliferation including p-p38, p-JNK and p-ERK, decreases the mRNA level of adenosine triphosphate-binding cassette transporter super-family ABCB1 and ABCG2 and the expression level of pro-survival Bcl-2 protein, and increases the expression level of the pro-apoptotic Bax protein compared with SNX-2112 and shSTAT3 alone groups ( 132 ). In addition, the combined treatment significantly reduces the tumor growth in in vivo ECSLCs xenograft tumor models compared to single treatments ( 132 ).…”
Section: Combinatorial Strategies In Treatment Of Solid Tumors Cscsmentioning
confidence: 99%
“…Here the dual treatment strongly inhibits the proliferation of ECSLCs, induces G2/M phase arrest and apoptosis of ECSLCs, significantly decreases the colony formation ability and the colony size of ECSLCs compared with shSTAT3 and SNX-2112 alone ( 132 ). On a molecular point of view, the combined treatment reduces the levels of phosphorylation of Hsp90 client proteins involved in cell proliferation including p-p38, p-JNK and p-ERK, decreases the mRNA level of adenosine triphosphate-binding cassette transporter super-family ABCB1 and ABCG2 and the expression level of pro-survival Bcl-2 protein, and increases the expression level of the pro-apoptotic Bax protein compared with SNX-2112 and shSTAT3 alone groups ( 132 ). In addition, the combined treatment significantly reduces the tumor growth in in vivo ECSLCs xenograft tumor models compared to single treatments ( 132 ).…”
Section: Combinatorial Strategies In Treatment Of Solid Tumors Cscsmentioning
confidence: 99%
“…This pathway play vital roles in multiple processes of human tumor, including proliferation, inflammation, and survival (Jin, 2020). As reported, the JAK2/ STAT3 pathway plays a regulatory role in the growth, metastasis of esophageal cancer cells (Liu et al, 2015;Xu et al, 2020). For example, phlorizin from sweet tea inhibits the growth, migration, aggressiveness, autophagy, and induces the apoptosis of esophageal cancer cells by antagonizing JAK2/STAT3 signaling pathway (Jia et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…69,70 The JAK-STAT pathway participates in the regulation of angiogenesis, inflammation, colony formation, stemness, invasion, motility, metastasis, EMT, cell cycle progression, growth, anoikis resistance, proliferation, migration, malignant formation, and sensitivity to chemotherapy and radiotherapy in EC cells and tumors. 7178 It has also been reported that patient survival, TNM stage, lymphatic metastasis, and degree of infiltration in patients with EC are associated with the expression, genetic, and activation statuses of this pathway. 7178 The NF-kappa B pathway has prognostic value in EC; it represses angiogenesis, metastasis, growth, inflammation, treatment resistance, carcinogenesis, tumorigenesis, and survival of EC cells and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…7178 It has also been reported that patient survival, TNM stage, lymphatic metastasis, and degree of infiltration in patients with EC are associated with the expression, genetic, and activation statuses of this pathway. 7178 The NF-kappa B pathway has prognostic value in EC; it represses angiogenesis, metastasis, growth, inflammation, treatment resistance, carcinogenesis, tumorigenesis, and survival of EC cells and tumors. 79 The programmed death-ligand 1 (PD-L1)/programmed death-1 (PD-1) checkpoint pathway may be important for the prediction of disease-free survival, overall survival, cancer relapse, treatment response rate and susceptibility, metastasis, lymph node invasion, tumor stage, and incidence of post-therapeutic adverse effects in patients with EC.…”
Section: Discussionmentioning
confidence: 99%